1994
DOI: 10.1021/bi00189a024
|View full text |Cite
|
Sign up to set email alerts
|

2H NMR Studies of Isomeric .omega.3 and .omega.6 Polyunsaturated Phospholipid Membranes

Abstract: The properties of aqueous multilamellar dispersions of [2H31]16:0-alpha 18:3 PC (1-[2H31]palmitoyl-2-cis,cis,cis-octa-9,12,15- trienoylphosphatidylcholine) and of [2H31]16:0-gamma 18:3 PC (1-[2H31]palmitoyl-2-cis,cis,cis-octa-6,9,12-trienoylphosphatid ylcholine) were compared by broadline 2H NMR spectroscopy. These isomeric phospholipids differ only in the location of the unsaturations in the sn-2 chain. The alpha 18:3 chain has double bonds at delta 9, 12, and 15 positions whereas in the gamma 18:3 chain they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 41 publications
4
20
0
Order By: Relevance
“…In previous investigations the molecular order of lipid hydrocarbon chains in the lamellar phase has been compared at the same reduced or absolute temperature. The reduced temperature scale is correcting for differences in the main phase transition temperature of lipids (see, e.g., Seelig and Seelig, 1977;McCabe et al, 1994;Holte et al, 1995). The question of which temperature scale to use becomes an issue, especially when one of the lipids in the series has a phase transition temperature that is much different from that of the others, as in the case of DSPC and unsaturated PCs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous investigations the molecular order of lipid hydrocarbon chains in the lamellar phase has been compared at the same reduced or absolute temperature. The reduced temperature scale is correcting for differences in the main phase transition temperature of lipids (see, e.g., Seelig and Seelig, 1977;McCabe et al, 1994;Holte et al, 1995). The question of which temperature scale to use becomes an issue, especially when one of the lipids in the series has a phase transition temperature that is much different from that of the others, as in the case of DSPC and unsaturated PCs.…”
Section: Discussionmentioning
confidence: 99%
“…Membrane properties are a consequence of lipid-lipid interactions, which are manifested over a broad range of length scales (7,8). At molecular scales (1-10 nm), lipid interactions determine molecular packing within membranes, characterized by structural parameters accessible by small-angle x-ray scattering (SAXS) (9,10) and by lipid order parameters obtained from solid-state NMR spectroscopy (10,11). The exact molecular packing within lipid bilayers is determined by the balance of forces between hydrophilic headgroups and hydrophobic chains, with the lipid headgroup having a dominant role in the case of saturated and monounsaturated acyl chains (10,12,13).…”
Section: Introductionmentioning
confidence: 99%
“…This powerful experimental technique provides an order parameter profile that describes the ordering of lipid acyl chains within the bilayer. A large order parameter means the motion of the acyl chains is strongly constrained, corresponding to tighter molecular packing, whereas small order parameters indicate more disorder and looser packing (8,(10)(11)(12). For this part of the study, we used deuterium-labeled lipids in PS/PC mixtures identified by x-ray scattering to be in the MLV-ULV transition range.…”
Section: Introductionmentioning
confidence: 99%
“…The precise structure of the membrane is labile and constantly changing. Nuclear magnetic resonance (NMR) studies have given us data on the mean orientations of hydrocarbon tails (Borle and Seelig, 1983;Rice and Oldfield, 1979;McCabe et al, 1994). NMR and neutron and x-ray diffraction have given us data on the mean orientations of the headgroups (Wiener and White, 1992b;Sanders, 1993).…”
Section: Introductionmentioning
confidence: 99%